Gender differences in the posterior circulations of the circle of Willis: A radioanatomical study - Abu Bakr, H Mossa; Tg Fatimah Murniwati, Tengku Muda; Zul Izhar, Mohd Ismail; Mohd Shafie, Abdullah (2015)
The complete arterial Circle of Willis (CoW) provides collateral circulation by its communicating arteries to meet the high cerebral metabolic demand. Based on its development, the posterior circulation of the CoW is divided into three types- adult, fetal and transitional types according to diameter of the posterior communicating artery in relation to the proximal segment of posterior cerebral artery. Many studies showed that the complete CoW is atypical in 40-70%o of population and it was associated with higher incidence of cerebral vascular diseases. Advancement in imaging studies like computed tomographic angiography (CTA) assists in studying the cerebral vessels and their anomalies. The main objective of this study was to identify the variations in the diameters of the CoW in patients who had undergone brain CTA. This is a retrospective study of the CTA databases from 123 patients who underwent brain CTA for suspected cerebral vascular diseases within year 2009-2011 in Hospital Universiti Sains Malaysia. The reconstructed three-dimensional images of the databases were examined thoroughly for the configuration of the CoW, absence of any vascular segment and presence of aneurysm. The same image series were converted to coronal, sagittal and transverse planes for measurement of the diameters of the different vascular segments of the CoW. The results showed no gender difference in vessels diameters, but the anomalies were significantly more in the posterior communicating arlery. Tlpes of posterior circulation showed that adult type was higher in males (rr<0.01, z test) but transitional and feotal types were higher in females (p<0.01, z test). In conclusion, there was male-female difference in tlpes of posterior circulation of the CoW.